Social Media Engagement Strategy in the Match Industry: A Case Study of PT. Lintas Cindo Bersama - Irawan, Wahyu Purno (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study explores how PT. Lintas Cindo Bersama, a traditional match manufacturing company in Indonesia, adopts social media engagement strategies to strengthen its communication and organizational responsiveness in the digital era. Using a qualitative case study approach, data were collected through in-depth interviews, online observations, and document analysis conducted over one year. The findings reveal that engagement in a low-involvement product industry is structured around three interrelated dimensions: maintaining consistency in managing social interactions, creating audience-specific content, and utilizing social media as a source of strategic insight. These strategies enable the company to cultivate authenticity, reliability, and responsiveness, fostering a meaningful relationship with audiences and reinforcing brand legitimacy. The study highlights that social media engagement, when systematically managed, functions not only as a marketing tool but also as a relational and strategic capability that supports organizational adaptation and learning. Theoretically, this research extends the Social Media Engagement Framework of Panagiotopoulos et al into the traditional manufacturing context, emphasizing the multidimensional nature of engagement as communication, sensing, and value co-creation. Practically, the results offer insights for legacy industries on how to leverage digital platforms to maintain relevance, innovate communication processes, and build sustainable stakeholder relationships. Overall, this study demonstrates that even in low-engagement sectors, strategic and authentic social media use can transform brand identity and organizational responsiveness in the face of ongoing digital transformation.